2005
DOI: 10.1152/japplphysiol.00622.2004
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of physical fitness, hormone replacement therapy, and hemostatic risk factors in postmenopausal women

Abstract: Relationship of physical fitness, hormone replacement therapy, and hemostatic risk factors in postmenopausal women. J Appl Physiol 98: 1341-1348, 2005. First published December 10, 2004 doi:10.1152/ japplphysiol.00622.2004.-This cross-sectional study evaluated the relationship of physical fitness, hormone replacement therapy (HRT), and hemostatic profiles at rest and after an acute bout of maximal exercise in 48 healthy postmenopausal women. Subjects were categorized by fitness and HRT user status into four g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…As disorders of coagulation and fibrinolysis have a great contribution in obesity related cardiovascular disorders (18,19). We found that weight loss program improves the parameters of systemic inflammation along with amelioration of coagulation disorders in obese subjects, our findings were in line with many previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…As disorders of coagulation and fibrinolysis have a great contribution in obesity related cardiovascular disorders (18,19). We found that weight loss program improves the parameters of systemic inflammation along with amelioration of coagulation disorders in obese subjects, our findings were in line with many previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…Both acute and chronic aerobic exercise have been eVective in eliciting improvements in Wbrinolytic potential, with increases in t-PA activity and decreases in PAI-1 activity levels (Stratton et al 1991, Szymanski et al 1996. Those who are classiWed as being more active, with high Wtness levels, generally have a greater Wbrinolytic response to acute exercise than their less Wt counterparts (DeSouza et al 1998;Szymanski et al 1996Szymanski et al , 2005Szymanski et al , 1994.…”
Section: Introductionmentioning
confidence: 99%
“…This complex pattern of changes in activation and deactivation in the haemostatic cascade has been described by many authors [25][26][27][28] ; however, no consistent picture is available yet. Acs et al 29 have recently carried out a meta-analysis comprising data from 6119 women on HRT and 24,974 non-users.…”
Section: Haemostatic Variablesmentioning
confidence: 63%